(untitled) (Biocenosis, 2012)
Peatland ecosystems are ecologically and socially relevant and they are an important educational resource to southern South America. This work shows an experience in environmental education developed for sixth and seventh grade students (primary school, Chilean educational system) focused on peatlands. Practical activities were carried out to strengthen educational process of natural environment protection and the understanding of the ecosystems from a local perspective. Detailed descriptions of activities and assessments are given.